Person-centered care in rehabilitation nursing: Integrating sexual health into transformative nursing practice - Teixeira , Filipe; Guerra, Nelson; Marques , Joana; Severino , Sandy; José , Helena; Sousa , Luís (Salud Integral y Comunitaria, 2026)
Introduction: McCance and McCormack’s Person-Centred Practice Theory is grounded in dignity, respect, and the active involvement of the person in their care. Rehabilitation Nursing in Portugal shares these principles, promoting autonomy and functionality throughout the life cycle. Sexuality, integrated within human functionality, constitutes an essential dimension of care, often neglected due to taboos and lack of specific policies.Objective: To critically analyse how the person-centred approach can be applied in Rehabilitation Nursing, emphasizing the integration of sexual health as a component of transformative care.Method: a theoretical-reflective study based on a literature review conducted between September and October 2025 using Google Scholar, EBSCOhost, and PubMed, employing MeSH and DeCS descriptors related to nursing care, rehabilitation, sexuality, and care models.Development: person-centred practice fosters ethical, empathetic, and collaborative relationships. In Rehabilitation Nursing, it reinforces personalized care and the recognition of sexuality as part of overall wellbeing. The Registered Nurses’ Association of Ontario supports this integration, promoting inclusive practices grounded in human rights. However, cultural and organizational barriers, such as the predominance of the biomedical model, hinder addressing sexuality by Specialist Rehabilitation Nurses.Conclusions: integrating sexuality within person-centred practice promotes ethical and humanized care. Overcoming barriers and investing in professional training are essential to establish inclusive, transformative practices supported by institutional policies.